«Customs visa-free travel» in the fight against money laundering and optimization of customs risks - Iryna Mykolaivna; Iryna Leonidivna; Tetiana Petrivna (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Ukraine constantly continues to move towards the consolidation of economic processes with the European Union, and the issue of rapid European integration as a whole is extremely relevant. Currently, a number of simplified procedures have been introduced with EU countries: «economic visa-free travel», transport and energy «visa-free travel» (all this contributes to the abolition of tariffs and quotas to simplify documentation, save money, avoid corruption and money laundering). Customs innovations allow Ukrainian businesses to get tools to take advantage of the benefits and simplifications of the joint transit procedure. The article defines that Ukraine’s accession in 2022 to the convention on the procedure of joint transit, the so-called «customs visa-free», will contribute not only to the simplification of customs procedures, but also to strengthening the security of customs transportation, the development of international trade, strengthening the fight against money laundering, transparency of export-import operations and ensuring the payment of customs payments to the budget. The use of a computerized transit system (NCTS) for «customs visa-free travel», in addition to simplifying customs clearance, allows for customs risk analysis, which generally contributes to improving the efficiency of customs risk management and combating money laundering.